2021
DOI: 10.1016/j.puhip.2021.100096
|View full text |Cite
|
Sign up to set email alerts
|

Uneven power dynamics must be levelled in COVID-19 vaccines access and distribution

Abstract: COVID-19 is one of the major global health threats of the 21 st century, causing unprecedented humanitarian crises worldwide. Despite concerted efforts to curb the spread of the disease, the pandemic continues to strain healthcare systems globally and a safe, highly effective, and globally acceptable and equitable vaccination program, together with pre-existing precautionary measures, is essential to effectively contain the outbreak. We commented on the need to level any uneven power dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…Interestingly, one of the reasons for non-acceptance of COVID-19 vaccine is the vaccine´s perceived high cost according to our findings. Access is also an important factor to be considered as regards the COVID-19 vaccine [ 40 , 41 ], and it is essential to translate the willingness to be vaccinated into actual vaccination decisions when the vaccine becomes available. Even though our study did not assess the willingness to pay for the COVID-19 vaccine, equitable access to vaccination is much-needed to quickly achieve herd immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one of the reasons for non-acceptance of COVID-19 vaccine is the vaccine´s perceived high cost according to our findings. Access is also an important factor to be considered as regards the COVID-19 vaccine [ 40 , 41 ], and it is essential to translate the willingness to be vaccinated into actual vaccination decisions when the vaccine becomes available. Even though our study did not assess the willingness to pay for the COVID-19 vaccine, equitable access to vaccination is much-needed to quickly achieve herd immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Discussions around perception of the COVID-19 vaccine and access to the COVID-19 vaccine are important to analyze so adjustments can be made in the delivery and approach to deploying the vaccine [ 31 ]. Our study found tweets that were explicitly related to equity and access.…”
Section: Discussionmentioning
confidence: 99%
“…Research demonstrates that the COVID-19 pandemic has disproportionately impacted communities of color due to socioeconomic status and lack of access [ 32 ]. Moreover, older Americans living in low-income households who are Black or of American Indian race have a higher associated risk of illness from COVID-19 [ 31 , 33 ]. Since equitable COVID-19 distribution is linked to removing the associated barriers [ 34 ], Twitter sentiment under the theme of equity and access communicates a relevance for vaccine equity and a priority of vaccine coverage to go to individuals at a higher risk of infection [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective vaccines should become global public goods, and first be provided to people in urgent need around the world ( 35 ). The ultimate victory in the global fight against the pandemic can only be achieved if countries around the world work together to ensure fair, equitable, and transparent distribution of the COVID-19 vaccine worldwide, and actively build a human health community ( 36 ). Moreover, relief resources including medical equipment, COVID-19 research and development, and medical personnel should be allocated inter-regionally according to the varying numbers of infections and severity of supply shortage among countries ( 37 ).…”
Section: Discussionmentioning
confidence: 99%